Reproduction accuracy of the range of movement range and pressure force in athletes - Bańkosz, Ziemowit; Pawlaczyk, Katarzyna; Lewandowski, Mieczysław (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Studies have proven that the level of proprioceptive ability is related to motor learning. Many authors also indicate the importance of proprioception in sports and have reported the existence of a correlation between kinesthetic differentiation abilities and success in different sports. Aim of Study. The aim of the study was to evaluate the accuracy of reproduction of the range of movement for forearm pronation and supination in the elbow joint as well as the level of hand pressure force in table tennis players, soccer players and non-training subjects. The study also attempted to examine changes in the level of this accuracy after six months of training. Material and Methods. The study was conducted on groups of table tennis players (10), soccer players (10), and non-training controls (10), aged 14.5 years. The participants undertook six tasks demonstrating their level of proprioceptive ability: accuracy of recreating pronation and supination of the forearm at the elbow joint; and accuracy of recreating hand pressure force. The test was carried out twice during the year. Results. The results revealed small differences between the groups after the first test and more significant differences after the second test. The soccer players showed a higher level of proprioceptive ability than the other two groups of participants. Conclusions. This study points to the significance of proprioceptive ability in soccer. The results of proprioceptive tasks are varied and depend on multiple factors, which is probably typical for this ability.
Keywords: proprioceptive ability; table tennis; soccer; reproduction of movement; joint position sense